Prospects and Achievements of Laparoscopic Cholecystectomy - Tashkarganovich, Mominov Alisher (Journal of Science in Medicine and Life, 2025)
Since the first laparoscopic cholecystectomy (LC) in 1985, there has been much advancement in laparoscopic surgery in terms of reduction in number and size of ports. We report a new technique of performing mini laparoscopic cholecystectomy using only three ports, 5 mm each. The indications of this procedure include GB polyps, GB dyskinesia, microlithiasis, and idiopathic pancreatitis. Case presentation: In this case report, we present a new technique that has been performed safely in a 49-year- old male patient with pancreatitis caused by microlithiasis. This was performed using a novel three port procedure consisting of only 5 mm ports, and he was discharged as a day case without complications. Informed patient consent was obtained. Conclusions: The fundamentals of this mini-LC technique remain the same as that of a standard laparoscopic chol- ecystectomy throughout the procedure. It is a feasible option in selected cases, and it has the potential to further aug- ment the inherent benefits of minimal access surgery namely less analgesia, improved cosmesis and faster recovery. Further trials will help ascertain its potential advantages.